A new biological and clinical resource for research into pregnancy complications: The Baby Bio Bank. (October 2016) - Leon, Lydia J.; Solanky, Nita; Stalman, Susanne E.; Demetriou, Charalambos; Abu-Amero, Sayeda; Stanier, Philip; Regan, Lesley; Moore, Gudrun E.
Abstract: About 20% of pregnancies are affected by some form of complication. Research has shown that anomalies in implantation, development, and growth of the fetus; ineffective nutrient exchange between mother and fetus due to placental dysfunction; and maternal problems such as hypertension or infection during pregnancy can all lead to adverse pregnancy outcomes. However, the molecular aetiology of such events remains poorly understood. Fetal growth restriction (FGR), recurrent miscarriage (RM), preterm birth (PTB), and pre-eclampsia (PE) are the most common pregnancy complications encountered in the UK and these outcomes can result in an array of morbidities in both mother and baby, and in the most severe cases in mortality. We need to know more about normal pregnancy and where the important triggers are for failure. This prompted us to collect a large set of biological samples with matching clinical data from over 2500 normal and abnormal pregnancies, for use in research into these conditions. This paper outlines the nature of these sample sets and their availability to academia and industry, with the intention that their widespread use in research will make significant contributions to the improvement of maternal and fetal health worldwide (http://www.ucl.ac.uk/tapb/sample-and-data-collections-at-ucl/biobanks-ucl/baby-biobank ). Highlights: The Baby Bio Bank is a new resource for research into complications in pregnancy. Over 50, 000 samples and linked clinical information for over 2500 pregnancies. Dedicated to the improvement of maternal and fetal health nationally and worldwide. The resource is open for applications from academic and industrial institutions.